2020
DOI: 10.1002/hep.31195
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐Induced Long Intergenic Noncoding RNA (LINC00665) Increases Malignancy Through Activating the Double‐Stranded RNA–Activated Protein Kinase/Nuclear Factor Kappa B Pathway in Hepatocellular Carcinoma

Abstract: Background and Aims The nuclear factor kappa B (NF‐κB) signaling pathway is important for linking inflammation and tumorigenesis. Here, we characterized an NF‐κB signaling activation–induced long intergenic noncoding (LINC) RNA in hepatocellular carcinoma (HCC), LINC00665, that contributes to the enhanced cell proliferation of HCC cells both in vitro and in vivo. Approach and Results LINC00665 physically interacts with the double‐stranded RNA (dsRNA)‐activated protein kinase (PKR), enhances its activation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Furthermore, PKR has been suggested to play an essential role in the antitumor activity of tumour suppressors, such as p53 and PTEN [43,44]. By contrast, PKR is able to induce cancer cell survival through NF-κB activation, and it has been reported that PKR is overexpressed and associated with malignancy in several cancers [43,45,46]. In this study, we showed suppression effect of PKR/eIF2α on ATC malignancy and found the regulatory mechanism for PKR via LINC00886.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, PKR has been suggested to play an essential role in the antitumor activity of tumour suppressors, such as p53 and PTEN [43,44]. By contrast, PKR is able to induce cancer cell survival through NF-κB activation, and it has been reported that PKR is overexpressed and associated with malignancy in several cancers [43,45,46]. In this study, we showed suppression effect of PKR/eIF2α on ATC malignancy and found the regulatory mechanism for PKR via LINC00886.…”
Section: Discussionmentioning
confidence: 51%
“…LINC00265 helps ZMIZ2 to stabilize β-catenin by acting as a sponge (and thereby inhibiting several miRNAs) in colorectal cancer (Zhu et al, 2019), and it can be used to predict poor prognosis in acute myeloid leukemia patients (Ma et al, 2018). It has been reported that LINC00665 increases the malignancy of hepatocellular carcinoma by activating the protein kinase R (PKR)/nuclear factor (NF)-κB pathway (Ding et al, 2020) and induce gastric cancer progression by activating the Wnt signaling pathway (Yang G. et al, 2014). Several of the nine lncRNAs were reported to be associated with cancer progression, but there have been few reports regarding glioma, and reports on how the lncRNAs interact with m6A-related genes have been even rarer.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing, dysfunctional lncRNAs are believed as key events for tumor development 21 . Recent studies have shown that LINC00665 exerts a carcinogenic role in many types of tumors 17 - 19 .…”
Section: Discussionmentioning
confidence: 99%
“…LINC00665 triggers lung carcinoma progression by sponging miR-98 and thus mediates the ERK signaling 16 . In addition, LINC00665 is also involved in the progression of gastric cancer and breast cancer 17 - 19 . Its biological function in OC is largely unclear.…”
Section: Introductionmentioning
confidence: 99%